Early growth and adult respiratory function in men and women followed from the fetal period to adulthood. - Canoy, D; Pekkanen, J; Elliott, P; Pouta, A; Laitinen, J; Hartikainen, A; Zitting, P; Patel, S; Little, M; Järvelin, MR (2007)
BACKGROUND: While some studies suggest that poor fetal growth rate, as indicated by lower birth weight, is associated with poor respiratory function in childhood, findings among adults remain inconsistent. A study was undertaken to determine the association between early growth and adult respiratory function. METHODS: A longitudinal birth cohort study was performed of 5390 men and women born full term and prospectively followed from the fetal period to adulthood. Weight at birth and infancy were recorded, and forced expiratory volume in 1 s (FEV(1)) and forced vital capacity (FVC) were assessed by standard spirometry at age 31 years. RESULTS: Adult FEV(1) and FVC increased linearly with higher birth weight in both men and women with no apparent threshold. After adjustment for sex, adult height and other potential confounders operating through the life course, every 500 g higher birth weight was associated with a higher FEV(1) of 53.1 ml (95% CI 38.4 to 67.7) and higher FVC of 52.5 ml (95% CI 35.5 to 69.4). These positive associations persisted across categories of smoking, physical activity and body mass index, with the lowest respiratory function noted among those with lower birth weight who were smokers, led a sedentary lifestyle or were overweight. Weight gain in infancy was also positively associated with adult lung function. CONCLUSION: Birth weight is continuously and independently associated with adult respiratory function. It is plausible that poor growth in early life may restrict normal lung growth and development, which could have long-term consequences on lung function later in life.